A personalized mobile patient guide system for a patient-centered smart hospital: Lessons learned from a usability test and satisfaction survey in a tertiary university hospital. (July 2016) - Yoo, Sooyoung; Jung, Se Young; Kim, Seok; Kim, Eunhye; Lee, Kee-Hyuck; Chung, Eunja; Hwang, Hee
Highlights: The mobile patient guide system with Bluetooth-based indoor navigation were evaluated in a tertiary hospital setting. The five main services were derived: scheduling, task information, 3D indoor navigation, outdoor navigation, questionnaire survey. Patients showed high satisfaction on the system, indicating their needs and usefulness. There were challenging issues on the task scheduling, the indoor navigation, and the usability. Abstract: Objective: The present study focused on the design, implementation, and evaluation of a personalized mobile patient guide system that utilizes smart phones, indoor navigation technology and a hospital information system (HIS) to address the difficulties that outpatients face in finding hospital facilities, recognizing their daily treatment schedule, and accessing personalized medical and administrative information. Materials and methods: The present study was conducted in a fully digitized tertiary university hospital in South Korea. We developed a real-time location-based outpatient guide system that consists of Bluetooth access points (APs) for indoor navigation, an Android-based guide application, a guide server, and interfaces with the HIS. A total of 33 subjects and 43 outpatients participated in the usability test (UT) and the satisfaction survey, respectively. Results: We confirmed that the indoor navigation feature can be applied to outpatient departments with precision using a position error test. The participants in the UT completed each scenario with an average success rate of 67.4%. According to the results, we addressed the problems and made improvements to the user interface by providing users with context-based guidance information. The satisfaction rating of the system was high, with an average score of 4.0 out of 5.0, showing its utility as a patient-centered hospital service. Conclusion: The innovative mobile patient guide system for outpatients is feasible and can be successfully implemented to provide personalized information with high satisfaction. Additionally, the issues identified and lessons learned from our experiences regarding task scheduling, indoor navigation, and usability should be considered when developing the system.